Female labour force participation in subSaharan Africa: A cohort analysis - Andreas Backhaus; Elke Loichinger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Female labour force participation rates have stagnated in sub-Saharan Africa since the turn of the millennium. This paper aims to explain this aggregate pattern by decomposing it into the labour supply behaviour of different birth cohorts and age groups. Using representative and repeated census data from a heterogeneous sample of sub-Saharan African countries, we show that declining female labour supply at early working age is explained by increasing school attendance among young female cohorts. Taking this heterogeneity into account, we find a positive association between female labour force participation and female educational attainment across the working age. Female education is further positively related to female employment in the nonprimary sector. Early motherhood, in turn, is associated with lower female schooling and a widening gender gap in labour supply. The higher investments in education by younger female cohorts, together with the demographics of sub-Saharan African countries, have implications for a potentially arising 'demographic dividend'.
Keywords: J11; J16; J21; J24; 330; labour supply; gender; sub-Saharan Africa; demographic dividend